Evidence for an enhancing effect of carbonated liquids on complex human swallowing behaviour. (13th March 2011) - Mastan, A; Michou, E; Mistry, S; Elshukri, O; Hamdy, S
Abstract : Introduction: Anecdotal clinical evidence supports the use of carbonated liquids for reducing pharyngeal transit time and the likelihood of aspiration in dysphagic patients compared to non-carbonated liquids.1 However, there is limited literature on the effects of carbonation on the physiology of swallowing behaviour. The aim of this study was thus to examine the effects of carbonated compared to non-carbonated solutions on swallowing behaviour, assessed by a novel reaction time task, 2 in healthy participants. Methods: Data was collected from 20 adult volunteers (mean age 25.7 years, 12 male). Volunteers swallowed an intrapharyngeal catheter with built-in pressure transducers to measure pharyngeal pressures. Subjects were asked to swallow either carbonated (condition A) or still (condition B) water, while performing 10 normal swallows (normally paced swallows), 10 fast swallows (swallowing as fast as possible) and 10 challenged swallows (swallowing within a limited time window). The conditions were performed twice and allocated in a pseudo-randomised manner. The trigger to swallow was an electrical pulse to the hand. A locally programmed laboratory interface system was used to record swallowing reaction times. Data were analysed with non-parametric Wilcoxon's test in SPSS 14. Results: Normal swallows: Despite a greater spread and wider IQR for carbonated water ((ms): still =875, carbonated =873), there was no difference between mean swallowing times between conditions ((ms): still = 1995, carbonated =2027, p= 0.50). Fast swallows: As with normal swallows, the IQR was larger with carbonated compared to still water ((ms): still=463, carbonated=588), however there remained no difference between the two conditions (means (ms): still =886, carbonated=879, p=0.74). Challenged swallows: By contrast to automated swallowing, carbonated water improved the number of correctly timed challenged swallows by ∼29% compared to still (mean (% correct) ±SD: still=31, carbonated=40, p=0.02). Across all swallowing tasks, there were no gender specific effects of carbonation. Conclusion: Carbonation appears to alter swallowing behaviour by favouring improvements in complex tasks over automated tasks. This has implications for the use of carbonation as a treatment option for dysphagic patients in preventing aspiration. These findings provide support for carbonation being a useful means of altering swallowing performance, potentially in those at risk of aspiration and lay the foundation for further studies accounting for pH, temperature and taste on swallowing function.